Oxygen consumption during sleep in atopic dermatitis. - Jenney, M E (1995)
Measurements of oxygen consumption (VO2) were made during sleep in 10 patients with atopic dermatitis. Two groups of healthy children acted as controls. All subjects were studied in bed in an environmental temperature of 24-26 degrees C, and sleep was confirmed during continuous electroencephalographic monitoring. Mean (SD) values of VO2 in sleeping patients who were not scratching ranged from 4.0 (0.4) to 7.4 (0.7), which was not statistically significantly different from control values which ranged from 3.24 (0.3) to 5.56 (0.4). During scratching (while asleep), which occurred in nine out of 10 patients with atopic dermatitis, the mean values of VO2 ranged from 4.5 (0.04) to 10.4 (2.7), and this was significantly higher than the non-scratching patients and the control values. Scratching during sleep in children with atopic dermatitis is associated with increased VO2.